TAHKO, Tuomas E. An Introducion to Metametaphysics. Cambridge: Cambridge University, 2015. 266 p. - Molick, Sanderson (Princípios: Revista de Filosofia (UFRN), 2018)
O livro do filósofo finlandês Tuomas Tahko, An introduction to Metametaphysics, recentemente lançado pela Cambridge University Press (2015) como um dos volumes da série Cambridge Introductions to Philosophy, fornece uma resposta à pergunta: Por que acrescentar um outro "meta" à palavra "metafísica" e tentar falar de uma metametafísica? De acordo com o autor, o termo "metametafísica" serve para designar a área da Filosofia que busca questionar a própria metodologia da metafísica, bem como seu propósito último. Deste modo, a metametafísica pode ser definida como o estudo dos fundamentos e metodologia da metafísica. O livro de Tuomas Tahko é uma notável obra que compila parte considerável do debate contemporâneo sobre o tema. [The book written by the finnish philosopher Tuomas Tahko, An introduction to Metametaphysics, recently published by Cambridge University Press as a volume of the series Cambridge Introductions to Philosophy, provides an answer to the question: why to add another "meta" to the word "metaphysics" and talk about a "metametaphysics"? According to the author, the term "metametaphysics" refers to the field of Philosophy which seeks to investigate the very methodology of Metaphysics, as well as its ultimate goal. Therefore, metametaphysics might be defined as the study of the foundations and methodology of Metaphysics. Tuomas Tahko's book is a notable contribution which compiles much of the contemporary debate on the theme.]